MOLECULAR DETECTION OF THE MEX EFFLUX PUMPS GENES IN EXTENSIVELY DRUG-RESISTANT AND PANDRUG-RESISTANT PSEUDOMONAS AERUGINOSA ISOLATED FROM IRAQI PATIENTS IN DIYALA - Lina Abdulameer S. Alsaadi (Scholar Express Journals, 2022)
The aim of this study was to determine the prevalence of Four clinicallyimportant efflux pumps including MexAB, MexXY, MexCD and MexEF in the Extensively Drug-resistant and Pandrug-resistant Pseudomonas aeruginosa isolated from clinical specimens in some hospitals in Diyala using a combination of resistance-phenotypic markers and PCR . This study was carried out during the period from February 2019 to August 2019. Clinical isolates (81) collected from patients suffering different infections. The isolates were diagnosed using classical methods and the VITEK 2 automated system followed by molecular detection using species-specific primer for 16S rRNA. All isolates were tested toward the different class of antimicrobials by using agar diffusion method using 18 clinically important antipseudomonal agents. The results of resistance were as following: piperacillin 74.07, ticarcillin 85.18%, Amoxicillin-Clavulanic acid 93.82%, Ticarcillin/clavulanic acid 71.60%, ceftriaxone 87.65% , cefotaxime 85.18% and ceftazidime 75.30%, cefepime 80.24%, streptomycin 90.12% ,gentamicin 85.18% ,tobramycin 65.43%, amikacin 56.79%, ciprofloxacin 67.90%, levofloxacin 72.83% , oflaxacin 69.13%, Aztreonam 50.61%, Imipenem 11.11% and Meropenem 23.45%. In this investigation, antibiotic susceptibility testing of the P. aeruginosa isolates showed that 20(24.69%),25(30.8%), 27(33.33%), and 9(11.11%) of the isolates were MDS,MDR, XDR and PDR, respectively. Based on the results from PCR, out of ninteen P.aeruginosa isolates(XDR and PDR), 19(100%) gave positive results for efflux system MexY gene , 18 isolates (94.7 % ) have MexB and MexF genes, while 17 isolates (89.47%) have MexD gene. This may indicate the prevalence these type of resistance in the current isolated bacteria.
Keywords: aeruginosa; XDR; PDR; Efflux